Rewarding or Sanctioning Performance? A critique on group dominance and counter-group dominance in public organizations - Mwesigwa, David (Journal of Governance and Accountability Studies, 2022)
Purpose: This study aimed to determine the synergy between performance rewards and performance sanctions. Research methodology: A desk research was adopted in which obtainable literature was consulted regarding the emerging themes and sub-themes of the study. Results: Results suggest that PRS are key elements in organizational management. Both monetary - and non-monetary rewards play significant roles but there is a greater move towards non-monetary rewards among modern-day organizations and public managers. Execution of performance sanctions is an essential aspect of enforcing performance though there are challenges inhibiting the process of identifying employees to be sanctioned. In this paper, it has been noted that direct supervisors are likely to suggest sanctions as a way of venting their anger against the unsuspecting victims. That is why it is imperative to reflect on whether the emphasis on performance rewards and sanctions is perpetuating group dominance and how probable the counter-group dominance group can abide by and/or ward off elements of subjugation in public organizations. Limitations: This study relied solely on secondary data yet adoption of primary data would yield significantly. Contribution: The results of this study are useful in guiding future field-based studies as well as those involved in human resource management in both the public sector and the private sector.